Unmanned Aerial Vehicles: A Survey on Monitoring Advancements for Port Infrastructure Applications - Konstantina Η. Chelioti; Christina N. Tsaimou; Vasiliki K. Tsoukala (Journal of Engineering, Project, and Production Management, 2023)
Ports play a significant role in the economic and social activities of the areas they serve. However, the adverse effects of the harsh and highly corrosive environments that ports operate in, along with phenomena related to the climate crisis and insufficient maintenance practices, increase port infrastructure's susceptibility to rapid degradation. This degradation can be aesthetic, functional, or structural and often leads to loss of serviceability at either a component (local and national) level or a global level. Moreover, many port structures have reached the limit of their lifetime, thus introducing the concept of extending their lifespan as a financially attractive alternative to constructing new facilities. Therefore, port operators pursue monitoring the structural integrity of the structures through an inspection plan aiming to reduce their maintenance and rehabilitation costs and ensure the safety of both the port infrastructure itself and human lives. Optimising monitoring approaches to enable damage detection and condition assessment can be achieved through the employment of Non-Destructive Testing (NDT) and Remote Sensing (RS) techniques. The current surge of using Unmanned Aerial Vehicles (UAVs) for both RS and NDT monitoring practices has proved promising since UAVs provide improved accessibility, increased inspection speed, and reduced safety hazards. The present paper is focused on investigating and evaluating the recent advances in UAV-driven port infrastructure monitoring. For this purpose, a comprehensive review of UAVs applications combined with NDT Infrared Thermography (IRT) and Ground Penetrating Radar (GPR) or RS Close Range Photogrammetry (CRP) and Light Detection and Ranging (LiDAR) is carried out to assess the potential and the limitations of the UAV-based monitoring approaches. This research provides valuable information on enhancing management strategies by upgrading port monitoring practices.